The determination of β-endosulfan and endosulfan sulfate in human serum with dialkylphosphate metabolites as urinary markers using LC-MS/MS electrospray ionization - Bergh, Werner (Division of Clinical Pharmacology, 2017)
Two separate bioanalytical methods were developed, validated and applied to determine agricultural exposure to organochlorine and organophosphorus pesticides using different biological matrices as reference sources. The method that was validated for the quantification of the organochlorine compounds was used to simultaneously determine β-endosulfan [6, 7, 8, 9, 10, 10- hexacloro-1, 5, 5a, 6, 9, 9a- hexahydro- 6, 9-methano-2, 4, 3-benzodioxathiepin-3- oxide] and one of its main metabolites, endosulfan sulfate, in human serum. In a second bioanalytical method, urinary dialkylphosphate metabolites have been assessed as markers to estimate the exposure to organophosphorus pesticides, focusing on three of the six organophosphorus urinary metabolites, namely dimethyl phosphate, dimethyl thiophosphate and diethyl phosphate. For both the bioanalytical methods, liquid-liquid extraction was used for sample preparation and high performance liquid chromatography with tandem mass spectrometry as detection method due to its high sensitivity and selectivity. Chromatographic separation for both bioanalytical methods was achieved by performing reverse phase chromatography on C18 analytical columns. Isocratic elution with a mobile phase composed of acetonitrile, methanol and water was employed for the analysis of the organochlorine compounds while the organophosphorus compounds were eluted using gradient elution with a mobile phase consisting of acetonitrile and 20 mM ammonium acetate. A triple quadrupole mass spectrometer equipped with an electrospray ionization source operating in the negative ionization mode was used for mass detection of all the analytes, employing multiple reaction monitoring as scan mode. Calibration standards and quality control samples for both analyses were prepared in the biological matrix in which the samples for each determination were collected, i.e. serum for the determination of the organochlorine compounds and stripped urine for the organophosphorus compounds. Deuterated internal standards were used in the bioanalytical method for the determination of the organophosphorus compounds whereas the organochlorine compounds were determined without the use of an internal standard due to unavailability of suitable internal standards. The calibration ranges for the determination of β-endosulfan and endosulfan sulfate were 0.8 ng/ml to 200 ng/ml and 0.117 ng/ml to 30 ng/ml, respectively, and 1.0 ng/ml to 30 ng/ml for the dialkylphosphate metabolites of the organophosphorus compounds. These sensitive and robust quantitation methods were successfully applied to quantify 219 serum and 187 urine samples that were collected from agricultural workers with the purpose to determine whether they were exposed to any of the investigated organochlorine or organophosphorus compounds. No traces of β-endosulfan and endosulfan sulfate were found in any of the serum samples that were analyzed, however, significant amounts of the three organophosphorus compounds dimethyl phosphate, dimethyl thiophosphate and diethyl phosphate were present in the urine samples.